Case-Based Reasoning for Selecting Study Program in Senior High School - Mulyana, Sri; Hartati, Sri; Wardoyo, Retantyo; Winarko, Edi (International journal of advanced computer science & applications, 2015)
One of the reasoning methods in expert system is Case-Based Reasoning (CBR). A problem is searching for past cases in the case base with thehighest similarity degree. This implies that calculation of similarity degree among the cases is an important aspect in CBR. In this study, an application of computer reasoning system based on CBR is developed for selecting study program in Senior High School (SHS). This aplication can be used to assist students for selecting study program. The cases used in the study include results of the intelligence test, student’s interest, and grades of several subjects.Each case in the case base will be calculated for the similarity degree with new cases entered. Furthermore, it is the cases with highest similarity degree that are recommended as solutions.